PENENTUAN SIFAT LISTRIK AIR PADA WADAH ALUMINIUM DAN BESI BERDASARKAN PENGARUH RADIASI MATAHARI - Yusuf Syetiawan; Sugianto '; Riad Syech (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted to determine the electrical properties of water in an aluminum and iron containers. The waters used were well and rain water using metaland aluminum containers. This research was conducted using an experimental method. The results showed that the best electrical properties was found from rain water in the aluminium container with its resistivity of 18.294m , electrical power of 0.00046 W, electrical energy of 2,941 J and electrical conductivity of 0.055 (1)m. The resultsindicated that greater solar radiation in the water could produce of electrical properties greater than that of water on the electrical properties of the electrical resistivity.The affecting factor of electrical properties of the rain water was concentration of Fe and Cu. The concentrations of Fe and Cu in rain water was 0,065 ppm and 0,050 ppm. It was also found that the smaller the concentrations of Fe and Cu levels in solution was the purer the solution.